Arthur Fischer-Colbrie student record - Fischer-Colbrie, Arthur, 1895-1968.
Student record from the Universitat Wien containing Sigmund Freud's signature.
Politician and writer.
In German.
Forms part of: Sigmund Freud collection.
Keywords: Freud, Sigmund, -- 1856-1939.; Authors; Politicians